Osmopriming duration in Araçá-boi seeds germination - Marcela Liege da Silva; Edvan Alves Chagas; Elias Ariel de Moura; Pollyana Cardoso Chagas; Oscar José Smiderle; Rosemary Vilaça Vilaça (Agro@mbiente On-line)
The Araca-boi is a native fruit of the Amazon region and its fruits have great potential for agro-industrial use due to the intrinsic characteristics of the pulp. The seeds are dormant and the primary cause could be due to the presence of inhibiting chemicals germination and can also be caused by the impermeability in tegument. The objective of this study was to assess the osmopriming efficiency promoted by Sucrose (C12H22O11) and Potassium Nitrate (KNO3 ) on germination of seeds of araca-boi in different immersion times. Thus, the seeds were osmoconditioned in following solutions: C12H22O11, KNO3 , KNO3 + C12H22O11 and H2 O, by period of 6, 12 and 24 h. Throughout of 70 days were evaluated the germination percentage and germination rate (index). The experiment is based on a completely randomized in a factorial analysis 4x3 with four replications of 10 seeds. The osmopriming of Araca-boi seed in KNO3 solution was shown to be efficient both to promote germination and the germination rate. The Araca-boi seeds osmoconditioned in KNO3 solution has an average efficiency of 99% in the germination percentage up to 70 days. The osmopriming period showed no influence on seed germination of the seeds of Araca-boi.